Does good corporate governance enhance accruals quality during financial crises?. Issue 4 (4th April 2016) - Aldamen, Husam; Duncan, Keith
Abstract : Purpose: The purpose of this study is to examine the efficacy of corporate governance systems in enhancing earnings quality during the recent global financial crisis (GFC). The literature provides insight into the corporate governance–accruals quality relationship during periods of relative financial stability. However, little is known about periods of unexpected financial shocks such as the GFC. Design/methodology/approach: The sample consists of 340 companies (1, 020 firm years) listed on the ASX during 2007-2009. Factor analysis is used to compute corporate governance factors. Seemingly unrelated regression (SUR) is used to test the impact of pre-GFC corporate governance on accruals quality during the GFC. Findings: Consistent with prior research, the findings suggest that good corporate governance is positively related to accruals quality before the GFC. More importantly, the impact of good governance intensifies during the GFC, where the mitigating role of governance is arguably under pressure. Furthermore, during the GFC, good corporate governance also affects the level of asset impairment. Research limitations/implications: The study provides empirical evidence that the relationship between good corporate governance practices and accruals quality is amplified during the GFC. The results support the efforts of market regulators to improve the governance of companies and make them stronger during financial crises. Originality/value: The study is an important addition to corporate governance research because it tests governance dynamics in a unique crisis period and establishes that corporate governance structures are effective when most needed.